2017
DOI: 10.20473/jbe.v5i1.2017.130-141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Respondent’s Characteristic with The Risk of Diabetes Mellitus and Dislipidemia at Tanah Kalikedinding

Abstract: ABSTRAKPenyakit tidak menular merupakan salah satu masalah kesehatan dunia dan Indonesia yang sampai saat ini masih menjadi perhatian dalam dunia kesehatan karena salah satu penyebab kematian. Beberapa jenis PTM yang dijumpai yaitu dislipidemia dan diabetes melitus (DM). Tujuan penelitian ini yaitu untuk menggambarkan hubungan umur, jenis kelamin, dan pendidikan dengan DM dan dislipidemia di Kecamatan Tanah kali kedinding surabaya Penelitian ini merupakan penelitian dengan desain cross sectional study. Populas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The results of the same study conducted on Halu Oleo University students showed that apart from smoking and consuming alcohol, risk factors for lack of physical activity (56.3%), and eating patterns based on frequency of eating/drinking trigger NCD for frequent consumption of types of food contains sugar (72.1%), contains sodium (salt) (35.0%), contains high fat (55.5%), while the type of drink containing caffeine with habit is a trigger factor for NCD, from risk factors This gave rise to diseases such as obesity (21.8%), and hypertension (13.9%) [20]. Lifestyle behaviors at risk for NCDs with the greatest proportion in adolescents are insufficient consumption of fruits and vegetables, excessive consumption of sodium, excessive consumption of fat, lack of physical activity and smoking [21]- [23]. Consuming excessive risky foods such as excessive junk food, consumption of sweet foods, processed foods with preservatives has a close relationship with the incidence of non-communicable diseases will trigger the emergence of nutritional disorders at a young age which can increase the risk of NCD [24]- [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the same study conducted on Halu Oleo University students showed that apart from smoking and consuming alcohol, risk factors for lack of physical activity (56.3%), and eating patterns based on frequency of eating/drinking trigger NCD for frequent consumption of types of food contains sugar (72.1%), contains sodium (salt) (35.0%), contains high fat (55.5%), while the type of drink containing caffeine with habit is a trigger factor for NCD, from risk factors This gave rise to diseases such as obesity (21.8%), and hypertension (13.9%) [20]. Lifestyle behaviors at risk for NCDs with the greatest proportion in adolescents are insufficient consumption of fruits and vegetables, excessive consumption of sodium, excessive consumption of fat, lack of physical activity and smoking [21]- [23]. Consuming excessive risky foods such as excessive junk food, consumption of sweet foods, processed foods with preservatives has a close relationship with the incidence of non-communicable diseases will trigger the emergence of nutritional disorders at a young age which can increase the risk of NCD [24]- [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to poor food consumption patterns, risk factors for lack of physical activity also greatly affect the incidence of NCDs in adolescence. One of the negative impacts of lack of physical activity is the emergence of diabetes mellitus and obesity or overweight [23]. According to the Law of the Republic of Indonesia Number 36 of 2009 concerning Health article 141 states that it is necessary to improve the quality Int J Public Health Sci ISSN: 2252-8806  of nutrition through food consumption patterns and physical activity in accordance with the General Guidelines for Balanced Nutrition (PUGS) in order to achieve good nutritional status so that the degree of public health increases.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan distribusi frekuensi senam kaki diabetik terlihat bahwa dimana responden yang kategori melakukan senam kaki diabetik sebanyak 59.5%. Hal ini sesuai dengan hasil penelitian yang dilakukan oleh (Widyasari, 2017) menunjukkan bahwa terdapat hubungan antara pendidikan terakhir dengan status diabetes seseorang. Kurang pengetahuan tentang senam kaki, dan apabila senam kaki tidak dilaksanakan dengan rutin dapat menyebabkan masalah neuropati diabetik.…”
Section: Pembahasan Senam Kaki Diabetik Pada Penderita Diabetes Melit...unclassified
“…Some risk factors for diabetes were age (45-69 years), marital status, hypertension, obesity, and family history [5]. Other factors that may increase diabetic prevalence include lifestyle, diet, work environment, exercise, and stress [6]. Some symptoms in diabetic patients are polyuria and polydipsia, weight gain, or loss.…”
Section: Introductionmentioning
confidence: 99%